2021
DOI: 10.3390/v13122516
|View full text |Cite
|
Sign up to set email alerts
|

Inositol Phosphates and Retroviral Assembly: A Cellular Perspective

Abstract: Understanding the molecular mechanisms of retroviral assembly has been a decades-long endeavor. With the recent discovery of inositol hexakisphosphate (IP6) acting as an assembly co-factor for human immunodeficiency virus (HIV), great strides have been made in retroviral research. In this review, the enzymatic pathways to synthesize and metabolize inositol phosphates (IPs) relevant to retroviral assembly are discussed. The functions of these enzymes and IPs are outlined in the context of the cellular biology i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 132 publications
0
3
0
Order By: Relevance
“…IP 6 interacts with the six-helix bundle structure and stabilizes the immature Gag lattice. IP 6 is also very crucial for the assembly of CA into the mature fullerene-like cone lattice [187][188][189][190][191][192].…”
Section: Maturation Inhibitorsmentioning
confidence: 99%
“…IP 6 interacts with the six-helix bundle structure and stabilizes the immature Gag lattice. IP 6 is also very crucial for the assembly of CA into the mature fullerene-like cone lattice [187][188][189][190][191][192].…”
Section: Maturation Inhibitorsmentioning
confidence: 99%
“…IP6 interacts with the six-helix bundle structure and stabilizes the immature Gag lattice. IP6 is also very crucial for assembly of CA into the mature fullerene-like cone lattice [187][188][189][190][191][192].…”
Section: Maturation Inhibitorsmentioning
confidence: 99%
“…IP6 was reported to interact with both the MA and CA domains of Gag. IP6 is released by the proteolytic cleavage of Gag and then stabilizes the mature capsid lattice in the course of maturation [ 31 , 32 , 33 , 34 , 35 , 36 , 37 ]. Our research group previously demonstrated that IP6 was able to bind to the MA approximately 10 times more strongly than IP3 [ 38 ].…”
Section: Introductionmentioning
confidence: 99%